Delegated acts in the field of European Union agricultural law - Tomkiewicz, Elżbieta (Przegląd Prawa Rolnego, 2021)
This article analyses delegated acts adopted by the European Commission under the Common Agricultural Policy for the years 2014–2020. Certain doubts arising from the interpretation of the hitherto practices have been highlighted. They concerned, particularly, the rulings on the interpretation of the concept “other than the essential elements of the legislative act” which has been reflected in many judgments issues by the European Court of Justice before the entry into force of the Lisbon Treaty. Other doubts related to the application of delegated acts concern the qualification of a given matter to the subject of regulation by a delegated act or an enforcement act. A separate discussion has been devoted to the far reaching autonomy of the European Commission regarding the adoption of delegated acts involving agricultural matters arising from the special position of the agricultural sector. The legislative activity of the European Commission with regards to the adoption of delegated acts under the urgency procedure in agricultural law has also been recognised.